2019
DOI: 10.1002/smll.201900975
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of and Insights into DNA “Codes” for Tunable Morphologies of Metal Nanoparticles

Abstract: The discovery and elucidation of genetic codes has profoundly changed not only biology but also many fields of science and engineering. The fundamental building blocks of life comprises of four simple deoxyribonucleotides and yet their combinations serve as the carrier of genetic information that encodes for proteins that can carry out many biological functions due to their unique functionalities. Inspired by nature, the functionalities of DNA molecules have been used as a capping ligand for controlling morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 168 publications
0
31
0
Order By: Relevance
“…Accordingly, diverse DNA‐encoded nanomaterials with different controlled shapes, morphologies, and properties were synthesized. [ 12–15 ] Functionalization and assembling of nanoparticles were attained on the basis of the high affinity of DNAs to metal nanointerfaces. [ 16–19 ] Fan group demonstrated poly adenine (polyA) was able to bind to GNPs with high affinity and can act as an effective anchoring group for facile preparation of DNA‐GNP conjugates.…”
Section: Figurementioning
confidence: 99%
“…Accordingly, diverse DNA‐encoded nanomaterials with different controlled shapes, morphologies, and properties were synthesized. [ 12–15 ] Functionalization and assembling of nanoparticles were attained on the basis of the high affinity of DNAs to metal nanointerfaces. [ 16–19 ] Fan group demonstrated poly adenine (polyA) was able to bind to GNPs with high affinity and can act as an effective anchoring group for facile preparation of DNA‐GNP conjugates.…”
Section: Figurementioning
confidence: 99%
“…Stabilizing agents (SAs) used for the preparation of nanoparticles in solution are of tremendous importance for the control of their size and shape [1–7] as well as for their colloidal stability [8–11] . Their role on the nanomaterial's properties is also established for magnetic, [8,12] optical, [13–15] thermoelectric, [16] catalytic properties, [17–21] and biocompatibility [22–24] .…”
Section: Introductionmentioning
confidence: 99%
“…It is well noted that ssDNA can be absorbed onto the gold surface in a sequence-dependent manner. Based on previous studies, dA (adenine), dC (cytosine), and dG (guanine) showed a much stronger binding affinity to gold surfaces than dT (thymine) . This property has been implemented to synthesize varied DNA-templated gold nanostructures or in DNA-based applications.…”
Section: Resultsmentioning
confidence: 99%
“…Based on previous studies, dA (adenine), dC (cytosine), and dG (guanine) showed a much stronger binding affinity to gold surfaces than dT (thymine). 34 This property has been implemented to synthesize varied DNA-templated gold nanostructures or in DNA-based applications. However, DNA-mediated morphological control of different types of ANPs on 2D materials in the absence of seeds has not been studied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%